Analysis of factors associated with adherence to drug treatment of patients with type 2 Diabetes mellitus in family health strategy units (Research, Society and Development, 2022)
Diabetes Mellitus is a chronic disease quite prevalent in the Brazilian population. Non-adherence to treatment implies serious complications for the patient, such as amputations and blindness. The objective of the present study was to identify the prevalence of adherence to drug treatment and the factors associated with non-adherence in patients diagnosed with type 2 Diabetes Mellitus (DM2), users of Family Health Strategies located in the city of Junqueirópolis, São Paulo. The sample consisted of patients, of both sexes, registered in the health system of Junqueirópolis, randomly drawn in each region of the city, making a total of 489 participants. The sociodemographic profile, clinical and subjective variables related to the treatment were addressed through a structured interview using a closed questionnaire. The Treatment Adherence Measure (MAT) was used to assess the individual's behavior in relation to the daily use of medication. Categorical variables are presented by their absolute and relative values, comparisons with independent variables were performed using the Chi-square test, adjusted for other confounding variables (gender, age). The results obtained show a high rate of adherence to drug treatment in the interviewed patients with DM2. There was a statistically significant association between the subjective variables presented and adherence to treatment, including having knowledge of the disease and regular monitoring of the condition, a fact that demonstrates the importance of the educational role of primary care in controlling the pathology.